Administración Por Resultados Y El Rendimiento Laboral En La Unidad Nacional De Almacenamiento Ep (Una-Ep) Planta Silos Ventanas. - Gutiérrez Mora, Xavier, A. (2015)
This research, examines the management by objectives and the impact on job performance of public servants of the Unidad Nacional de Almacenamiento EP (UNA- EP) in Ventanas city, valuing the factors that affect job performance. This study as sources of information is quantitative type, through research data was quantified attention in the Unidad Nacional de Almacenamiento EP (UNA- EP) users (farmers) of the same. A non-experimental research, where observation was used to find existing situations, and not caused by the researcher, that is the situation as it was presented was applied was observed. The interview and surveys served as a research technique, to internal and external users having been applied. Plan development of human talent to increase work performance of officials of the Unidad Nacional de Almacenamiento EP (UNA- EP) Planta Silos Ventanas EP (UNA-EP) is proposed.